Glyphosate runoff and its occurrence in rainwater and subsurface soil in the nearby area of agricultural fields in Argentina. (June 2019) - Lupi, Leonardo; Bedmar, Francisco; Puricelli, Marino; Marino, Damián; Aparicio, Virginia C.; Wunderlin, Daniel; Miglioranza, Karina S.B.
Abstract: Glyphosate-based products are among the most important herbicides applied to enhance the production of food commodities, leading to the worldwide spread of this herbicide. The main goal of this work was to evaluate the off-site transport of glyphosate in a runoff experiment. A micro-plot experiment was conducted to assess the retention, leaching and runoff of glyphosate under rainfall simulation. Glyphosate losses due to spray drift were estimated. Concentrations of glyphosate and AMPA were determined in rainwater and subsurface soil from agricultural and riparian zones. Analyses were performed with UHPLC-MS/MS. Experimental results demonstrated that 88.1% of the applied glyphosate was retained in the surface soil layer (0–9 cm). Glyphosate leaching was negligible compared to its runoff (3.9%) and spray drift (6.9%). Thus, the risk of groundwater pollution would be lower in comparison to that of both surface waters and rainwater. Moreover, under field conditions, glyphosate and AMPA were detected in 52% of the rainwater samples and glyphosate was detected up to 1 m in both soil profiles. Although the experimental application was made with hand-held knapsack under low wind condition to minimize glyphosate aerial dispersion, the spray drift was the main source of glyphosate off-site transport, degrading air quality and rainwater for human consumption. The balance among spray drift, runoff and soil absorption of glyphosate when it was sprayed close to the soil surface (hand held equipment), demonstrated the importance of spray drift in mass balance studies during runoff and leaching experiments with glyphosate. Graphical abstract: Image 1 Highlights: Glyphosate and AMPA were largely retained in the surface soil layer. Glyphosate loads were similar for spray drift and runoff. Trace levels of glyphosate were detected at the subsurface of the riparian zone. Glyphosate and AMPA in rainwater exceeded limits for safe human consumption.